Eco-friendly and sustainability assessment of technologies for nutrient recovery from human urine—a review - Saliu, Toyin Dunsin; Oladoja, Nurudeen Abiola; Sauvé, Sébastien (Frontiers in Sustainability, 2024)
Nitrogen (N), phosphorus (P), and potassium (K) represent the primary components of commercial NPK fertilizer and are primarily derived from finite resources through complex and expensive processes. To ensure global food security, the development of sustainable and eco-friendly procedures for fertilizer production has gained attention. Humans generally excrete urine containing 11 g of N/L, 0.3 g of P/L of P and 1.5 g of K/L, which benefit plant growth. The recovery of these essential plant nutrients from human urine has become the focal point of increasing research endeavours. Despite the potential advantages of nutrient recovery from urine, this process is complicated, and the economic implications are substantial.Furthermore, human urine may harbour undesirable contaminants, such as pathogens, pharmaceutical residues, hormones, and elevated salt levels, which could be disseminated into the environment in agriculture.This study appraised various emerging technologies for nutrient recovery from human urine, considering their challenges, environmental impact, economic viability, and the overall sustainability of the processes. This review elucidated that most nutrient recovery technologies demonstrated elevated efficiency in nutrient recovery. Nevertheless, a recurrent oversight involves neglecting the potential transfer of contaminants and pathogens into environmental matrices. The complexity of these processes and their economic feasibility vary, with some proving intricate and economically unviable. Given that no singular technology fully mitigates these challenges, integrating two or more technologies appears imperative to address drawbacks and enhance overall system performance.